2006
DOI: 10.1017/s0959270906000219
|View full text |Cite
|
Sign up to set email alerts
|

The endemic Bawean Serpent-eagle Spilornis baweanus: habitat use, abundance and conservation

Abstract: The Bawean Serpent-eagle Spilornis baweanus is endemic to the 190 km 2 island of Bawean in the Java Sea (Indonesia) where it is the only resident diurnal raptor. A 15 day study in 2002 revealed that the species is present in small numbers throughout the island. The eagle's abundance was assessed by an island-wide survey and by sampling 28 1 km 2 plots covering five habitat types. There was a strong positive correlation between abundance and contact time in plots. Compared with other habitat types, the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…Century (Oberholser, 1917;Hoogerwerf, 1966Hoogerwerf, , 1967. Since these surveys, however, little ornithological work has been carried out on the island, except for a 2002 study of owls and birds of prey by Nijman (2004Nijman ( , 2006. He added three new species of large predatory birds to the island's list, bringing the historical total to 55, but did not comment on the status of species in other families.…”
Section: Bawean Expeditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Century (Oberholser, 1917;Hoogerwerf, 1966Hoogerwerf, , 1967. Since these surveys, however, little ornithological work has been carried out on the island, except for a 2002 study of owls and birds of prey by Nijman (2004Nijman ( , 2006. He added three new species of large predatory birds to the island's list, bringing the historical total to 55, but did not comment on the status of species in other families.…”
Section: Bawean Expeditionmentioning
confidence: 99%
“…Based on interviews with residents, Nijman (2006) reported that pellet guns became common on the island in the late 1990s, and that bird hunting is common. Additionally, the island is relatively close to Java, where many species are in high demand as cage-birds (Eaton et al, 2015).…”
Section: Bawean Expeditionmentioning
confidence: 99%
“…The population of raptors is threatened by illegal trade, hunting, habitat destruction and the use of pesticide (Rodriguez-Estrella et al, 1998;van Balen et al, 2000;Nijman, 2006;Supriatna, 2012). According to BirdLife International (2015), major threats are the increase in human population, weak law enforcement, and low public awareness about raptors conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Популяциям хищных птиц угрожает не-легальная торговля, браконьерство, раз-рушение естественных местообитаний и использование пестицидов (RodriguezEstrella et al, 1998;van Balen et al, 2000;Nijman, 2006;Supriatna, 2012). По данным BirdLife International (2015), основные угрозы хищным птицам исходят от уве-личения численности населения, слабой правоохранительной деятельности и низ-кого уровня осведомлённости обществен-ности об охране хищных птиц.…”
Section: Introductionunclassified
“…Although the breeding behavior and habitat preferences of the Crested Serpent-Eagle have been documented for several subspecies across Asia, including those in China, India, Japan, and Taiwan (Morioka 1995, Ueta and Minton 1996, Lin et al 1998, van Balen 1998, Zhang 2000, Sano 2003, Chou et al 2004, Chou 2005, Lin 2005, Nijman 2007, little is known about population density, home-range size, and habitat preferences of the Formosan Crested Serpent-Eagle (but see Chou andShiu 2007, Chou et al 2012). Since this knowledge is important for animal ecology (Manly et al 1993, Conner et al 2003, population ecology (Newton 1979), and conservation (Bildstein et al 1998, Thiollay 1998a, Sergio et al 2008, we used observations and radio-tracking to estimate population density and home-range size and to investigate the habitat use of the Formosan Crested Serpent-Eagle.…”
mentioning
confidence: 99%